A comprehensive analysis on the effect of shape on the microwave heating dynamics of food materials. (February 2017) - Bhattacharya, Madhuchhanda; Basak, Tanmay
Abstract: A detailed theoretical analysis has been carried out to investigate the effect of the shape of the sample on the microwave heating dynamics of food materials. The food materials are divided into four groups based on the microwave propagation parameters and the heating dynamics of each group of materials have been simulated for one representative material involving semiinfinite cylindrical samples of circular and square shapes. The selection of the two shapes (circular and square) is to investigate the influence of the presence of sharp corners in the square samples on the microwave propagation dynamics within the food materials. The detailed study reveals that the presence of the corner can have a pronounced effect (either beneficial or detrimental) on the spatial heating dynamics for the intermediate and thick samples based on the propagation parameters and orientation of microwave sources with respect to the corner. Industrial relevance: Microwave processing of food materials strongly depends on shapes of the materials as microwave propagation within food materials can be altered based on various incidence and reflected waves which are largely dependent on the structure of food materials. In general, spatial non-uniformities of heating patterns occur during microwave processing and there are no generalized guidelines available for industrial food processing. The entire spectrum of food materials can be categorized in four groups and generalized heating patterns can be deduced apriori for each group of food materials. Numerical simulation results predict that the shapes or cross section of food materials (squares, circular etc.) play important roles as the square shape exhibits interesting corner heating patterns and a trivial circular sample may not be a recommended food sample for efficient industrial microwave processing. Highlights: Microwave heating is simulated for a variety of circular and square food samples. Effect of shape on overall heating rate and spatial heating dynamics is analyzed. Analysis includes all four groups of food materials showing entire heating spectrum. Results reveal interesting corner effect in various square food samples. Results show that circular samples may not be the best configuration for some cases.